Is there a need to phase out replacement blood donors by voluntary blood donors in hospital based blood transfusion services? - Praneeta Jaswant Singh; Hitesh Bhatt (Iraqi Journal of Hematology, 2017)
Background: Providing safe blood for transfusion is a responsibility of every blood bank. Screening for transfusion-transmissible infections (TTI) is one of the ways to ensure safety of blood and its products. Prevalence of TTI varies in different countries. It is low in developed countries whereas it is higher in developing countries. Aims And Objectives: This study was carried out to access percentage of blood collected from the first-time voluntary blood donors (VBD) and family/replacement donors (RD) and to access safety of RD by comparing seroprevalence of TTI among voluntary and RD. Materials And Methods: Over 1 year, donors were studied for the type of donation (voluntary or replacement) made at our blood bank. All donors were screened for human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), syphilis, and malaria. Comparison of the prevalence of TTI among voluntary and RD was done by entering data into Microsoft Excel 2007 software and using Chi-square tests. Results: Out of total 850 first-time donors, voluntary donors were 109 (12.82%) and RD were 741 (87.18%). Overall seroprevalence of HIV, HBV, HCV, syphilis, and malaria was 0, 23 (2.70%), 12 (1.41%), 7 (0.82%), and 0, respectively. Prevalence of TTI among voluntary donors was very low. All donors were seronegative HIV and malaria. Prevalence of HBV, HCV, and syphilis was higher in RD. Conclusion: Data highlight that RD contributed major source of blood supply in hospital-based blood transfusion services and the prevalence of TTI was higher among them in comparison to first-time voluntary donors. Thus, efforts should be made to increase the number of VBD.